2023
DOI: 10.1021/acs.orglett.3c01254
|View full text |Cite
|
Sign up to set email alerts
|

Construction of the Tetracyclic Framework of Sulfur-Containing Discorhabdin-Type Alkaloids

Abstract: Herein, we report an efficient synthetic method for constructing the tetracyclic scaffold of sulfur-containing discorhabdin-type alkaloids. The key to success is the BF3•Et2O-promoted dienone-phenol-type rearrangement/sulfur insertion cascade reaction, which converts the common and readily available N,O-acetal-bridged tetracyclic framework to the labile and synthetically challenging N,S-acetal-bridged tetracyclic framework in a single step. Additionally, the hypervalent iodine promoted intramolecular oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…As a result, unbridged discorhabdins have received the most synthetic attention. While several formal and total syntheses of achiral discorhabdin C ( 2 ) [6] and racemic discorhabdin E ( 3 ) [6c] have been reported, the numerous synthetic studies on pyrroloiminoquinones have mostly focused on preparing the tricyclic core, found in makaluvamines and related compounds, [7,8a] or forming the spirodienone [8a,9,10] . The synthesis of discorhabdin A ( 4 ) by Kita and co‐workers [11] remained the sole reported example of an asymmetric synthesis of a discorhabdin for two decades.…”
Section: Figurementioning
confidence: 99%
“…As a result, unbridged discorhabdins have received the most synthetic attention. While several formal and total syntheses of achiral discorhabdin C ( 2 ) [6] and racemic discorhabdin E ( 3 ) [6c] have been reported, the numerous synthetic studies on pyrroloiminoquinones have mostly focused on preparing the tricyclic core, found in makaluvamines and related compounds, [7,8a] or forming the spirodienone [8a,9,10] . The synthesis of discorhabdin A ( 4 ) by Kita and co‐workers [11] remained the sole reported example of an asymmetric synthesis of a discorhabdin for two decades.…”
Section: Figurementioning
confidence: 99%